Transient pseudohypoaldosteronism in infancy mainly manifested as poor appetite and vomiting: Two case reports and review of the literature - Tuoheti, Yueerlanmu; Zheng, Yucan; Lu, Yan; Li, Mei; Jin, Yu (Frontiers in Pediatrics, 2022)
Introduction: Transient Pseudohypoaldosteronism (TPHA) is a very rare condition that is usually secondary to urinary tract malformations (UTM) and/or urinary tract infection (UTI). The clinical characteristics of TPHA are mainly hyperkalemia, hyponatremia, metabolic acidosis, and the elevation of plasma aldosterone level. Since the predominant manifestations of TPHA patients are digestive tract symptoms, such as poor appetite, vomiting, and weight gain, it is easily misdiagnosed as digestive tract diseases. Case reports: Two children with poor appetite and vomiting were admitted to the Department of Gastroenterology, Children's Hospital affiliated to Nanjing Medical University, from 2020 to 2021. Laboratory test results of these two children revealed hyponatremia (< 135.00 mmol/L), hyperkalemia (> 5.50 mmol/L), hyperaldosteronism (> 180.00 ng/L). And genetic tests in both cases showed no abnormalities. Magnetic resonance urography (MRU) examination of the first case displayed left hydronephrosis and ureteral obstruction without urinary tract infection, and management with salt supplementation and potassium reduction was effective. The patient was followed up for 8 months with no evidence of TPHA and did not undergo any surgical interventions. Meanwhile, MRU of the second case indicated bilateral hydronephrosis, ureteral obstruction, and urine culture was positive for Morganella morganii subspecies. Moreover, salt supplementation, potassium reduction, and antibiotic treatment were effective. After the urethral deformity was corrected, the patient was followed up for 4 months, during which TPHA was not observed. Conclusion: TPHA should be considered in children younger than 6 months of age presenting with vomiting, poor appetite, unexplained hyponatremia, hyperkalemia, elevated aldosterone levels, and urethral malformation or urinary tract infection. Furthermore, attention should be paid to whether salt supplementation or anti-infection therapy is effective.